Extended adjuvant endocrine treatment for premenopausal women: A Delphi approach to guide clinical practice - Buono, Giuseppe; Arpino, Grazia; Del Mastro, Lucia; Fabi, Alessandra; Generali, Daniele; Puglisi, Fabio; Zambelli, Alberto; Cinieri, Saverio; Nuzzo, Francesco; Di Lauro, Vincenzo; Vigneri, Paolo; Bianchini, Giampaolo; et al. (Frontiers in Oncology, 2022)
The use of an aromatase inhibitor (AI) in combination with ovarian function suppression (OFS) has become the mainstay of adjuvant endocrine therapy in high-risk premenopausal patients with hormone receptor-positive breast cancer. Although five years of such therapy effectively reduces recurrence rates, a substantial risk of late recurrence remains in this setting. Multiple trials have shown that extending AI treatment beyond five years could offer further protection. However, as these studies comprised only postmenopausal patients, no direct evidence currently exists to inform about the potential benefits and/or side effects of extended AI + OFS therapies in premenopausal women. Given these grey areas, we conducted a Delphi survey to report on the opinion of experts in breast cancer treatment and summarize a consensus on the discussed topics. A total of 44 items were identified, all centred around two main themes: 1) defining reliable prognostic factors to pinpoint premenopausal patients eligible for endocrine therapy extension; 2) designing how such therapy should optimally be administered in terms of treatment combinations and duration based on patients’ menopausal status. Each item was separately discussed and anonymously voted by 12 experts representing oncological institutes spread across Italy. The consensus threshold was reached in 36 out of 44 items (82%). Herein, we discuss the levels of agreement/disagreement achieved by each item in relation to the current body of literature. In the absence of randomized trials to guide the tailoring of extended AI treatment in premenopausal women, conclusions from our study provide a framework to assist routine clinical practice.